The Association Between the Concentration of Serum Magnesium and Postmenopausal Osteoporosis - Chang, Jinlei; Yu, Degang; Ji, Jindou; Wang, Ning; Yu, Shengwen; Yu, Bo (Frontiers in Medicine, 2020)
Background: Osteoporosis is the most common and widespread chronic skeletal metabolic disease in the world and can lead to catastrophic fractures. Therefore, it is important to look for factors that can be modified or controlled to prevent osteoporosis. Although serum Mg is believed to be associated with osteoporosis in many individuals, there are conflicting reports on the association between serum Mg and osteoporosis. Therefore, this meta-analyses aimed to explore the association between the concentration of serum Mg and osteoporosis as well as that between the concentration of serum Mg and osteopenia. Methods: Articles were searched in PubMed. We also reviewed the reference lists of the relevant publications and reviews as of December 2019. Finally, 11 eligible studies involving 2,776 postmenopausal women were selected. We performed subgroup analysis, and publication bias was assessed. Results: According to the forest plot analysis, postmenopausal women with osteoporosis had a lower concentration of serum Mg than normal controls [standardized mean difference (SMD) = −0.56, 95% confidence interval (CI) = −1.02 to −0.09]. However, this result was not applicable to those with osteopenia (SMD = −0.30, 95% CI = −0.69 to 0.09). The subgroup analysis by geographical location found a similar pattern in European postmenopausal women with osteoporosis (SMD = −0.73, 95% CI = −1.322 to −0.143), but not in Asian (SMD = −0.007, 95% CI = −0.381 to 0.394). The subgroup analysis by site of bone mineral density (BMD) showed the serum Mg concentration of postmenopausal women with osteoporosis (BMD of femur) was lower than in healthy controls (SMD = −0.44, 95% CI = −0.77 to −0.12), and BMD of the spine group had the same conclusion (SMD = −0.78, 95% CI = −1.36 to −0.19). Besides, the serum Mg concentration of postmenopausal women with osteoporosis was lower than that of the normal bone mass group in the studies those included more than 50 postmenopausal women with osteoporosis (SMD = −0.57, 95% CI = −1.04 to −0.11). We also found postmenopausal women under the age of 60 with osteoporosis had a lower concentration of serum Mg than the healthy controls (SMD = −0.61, 95% CI = −1.09 to −0.13). Conclusion: Postmenopausal women with osteoporosis have a lower concentration of serum Mg. However, the association between the concentration of serum Mg and osteopenia needs further confirmation.